Studi Komparatif terhadap Qanun Aceh tentang Hukum Jinayat dan Enakmen Jenayah Syariah Selangor Malaysia - Ahmad Bahiej (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2014)
This paper compares the substance of Aceh Qanun of Jinayat and Enakmen Jenayah Syaria Selangor Number 9/1995. Aceh Qanun substance and Enakmen Jenayah Syaria Selangor Malaysia have some similarities among criminalize spreader cult, not perform Friday prayers, not respect Ramadan, not Islamic dressing in public places, alcohol or gambling, seclusion, liwath/same-sex relationships, qazaf, prostitution, pimping, adultery/extramarital intercourse. The both rule are applied only to Muslims and applicable in certain region (province/state). Compared with Aceh Qanun, Enakmen Jenayah Syaria Selangor regulates more crimes. Nevertheless, Aceh Qanun threatening criminal sanctions heavier than Enakmen Jenayah Syaria Selangor and opportunities for non-Muslims voluntarily subjecting himself to the by laws. The principle of lex posteriore derogat legi inferiore is not apply to Aceh Qanun. Meanwhile, Enakmen Jenayah Syaria Selangor to enforce the Sharia principle of lex posteriore derogat legi inferiore.